Serum Fibroblast Growth Factor 21 Levels Are Correlated with the Severity of Diabetic Retinopathy - Yuan Lin; Ye-cheng Xiao; Hong Zhu; Qing-yan Xu; Lei Qi; Yu-bin Wang; Xiu-juan Li; Ma-li Zheng; Rui-sheng Zhong; Yi Zhang; Xiang-dong Xu; Bo-le Wu; et al. (Journal of Diabetes Research)
The aim of the study was to assess serum fibroblast growth factor 21 (FGF21) concentrations in Chinese type 2 diabetic patients with and without retinopathy and to assess the association between FGF21 and the severity of retinopathy. 117 diabetic patients were compared with 68 healthy controls. Fasting blood glucose, serum total cholesterol, serum triglycerides, serum insulin, and serum FGF21 levels were estimated. FGF21 concentrations in the patients were significantly higher than those in control. In the patient group there was a significant positive correlation between FGF21, insulin level, and homeostasis model assessment index. Serum FGF21 concentrations in patients with proliferative diabetic retinopathy or nonproliferative diabetic retinopathy were significantly higher than those in patients without diabetic retinopathy. When the presence of diabetes was defined as the final variable in the conditional logistic regression model with the FGF21 concentration as the continuous variable, FGF21 was significantly involved in the model. This study shows that the increase in serum concentration of FGF21 was associated with the severity of diabetic retinopathy and suggests that FGF21 may play a role in the pathogenesis of diabetic retinopathy and its degree.